The Sufis of Karacadağ and The Followers of Shah Ismail Hatayi (Journal of Alevism-Bektashism Studies, 2024)
To better understand the formation process of a state, it is both important and necessary to analyze the methods the founder of that state used to seize power and to evaluate the outcomes of these methods. The Safavid State is no exception to this. The Safavids initially formed around a Sufi order as a mystical movement, and after almost two centuries of expanding their activity, they ultimately succeeded in emerging as a state on the historical stage. Indeed, it is essential to recognize the groups involved in the formation process, especially during its establishment. This will help clarify the characteristics and nature of the state during its formative stage. In this context, the main aim of this study is to examine the role of the Sufis settled in the Karacadağ region and their involvement in the process of Shah Ismail I’s establishment of the Safavid State. Research related to the Safavid period generally mentions the Karacadağ Sufis alongside the Kızılbaş and Talish tribes, but no detailed study has been conducted so far on their influence in the rise of the state. Therefore, this article carries significant and innovative importance. In this study, information obtained from primary sources, archival documents, and fieldwork is utilized to gather scattered data and analyzed using a qualitative-analytic method. The findings reveal that, like the Anatolian Turkmens, the Karacadağ Sufis were among the earliest disciples of the Safavi Order. They supported Shah Ismail and his father in various ways and continued to serve the Safavid kings with loyalty even after the establishment of the state. It seems that the small geographical size of the Karacadağ region and its relatively low population compared to the densely populated Anatolian Kızılbaş tribes led to the overshadowing or even neglect of their role in the emergence of the Safavid State. While addressing this gap in the research, the study will also identify the religious characteristics of the Turkmens still living in the region and reveal the underlying religious reasons for their assistance in the establishment of the Safavid State.